OPTIMAL ROUTE OF AIRCRAFT FOR AGROAVIATION WORKS - Шаріфов, Ф.А.; Юн, Г.М.; Кандиба, Г. Ю. (Science-based technologies, 2014)
The paper is addressed to the problem for finding a minimum route of aircraft during tilling a filed by required chemicals. First it is shown that for the field of rectangle form a minimum route of the aircraft can be reduced to the traveling salesman problem on the simple undirected graph constructed by special way. Then it is also noted that the similar reduction is suitable with respect to field of any form. The paper contains two well known mathematics formulation of the travelling salesman problem on graphs. First model is written in the term of graph vertices degree; and second model includes some constraints as in assignment problem of the matrix formulation. Each model can be used for solving travelling salesman problem by using appropriated program code which guaranteed some alternative choice for users.